2014
DOI: 10.15640/jaes.v3n4a3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Good Agricultural Practices (GAP) Compliance by Small Farmers in Kentucky: Assessing Microbial Quality of Produce

Abstract: In recent years the number of bacterial food-borne outbreaks associated with contaminated produce has increased substantially. Escherichia coli(E.coli) continues to contribute to the majority of foodborne illnesses. With more small farmers starting organic production and given a wide range of organic production practices, there is a vulnerable segment which demands continuous microbial safety assessments. In the current study, twenty small produce farms from fourteen counties in Kentucky participated in a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…carrots as produce growing under the surface, leafy greens as produce growing at surface level, and tomatoes as produce growing above the surface level. As reported earlier [32], most Enterobacteriaceae were detected (18.5%) on carrots, followed by tomatoes and leafy greens. Table 3: Occurrence (%) Enterobacteriaceae from supermarket samples and their resistance profile.…”
Section: Retail Samplessupporting
confidence: 83%
See 1 more Smart Citation
“…carrots as produce growing under the surface, leafy greens as produce growing at surface level, and tomatoes as produce growing above the surface level. As reported earlier [32], most Enterobacteriaceae were detected (18.5%) on carrots, followed by tomatoes and leafy greens. Table 3: Occurrence (%) Enterobacteriaceae from supermarket samples and their resistance profile.…”
Section: Retail Samplessupporting
confidence: 83%
“…These produce types were chosen based on a previous study in which higher contamination of E. coli was observed in produce samples that grew at or below the surface of the plant compared to produce samples that grew above the surface [32]. Each vegetable was chosen as representative of the placement, i.e.…”
Section: Retail Samplesmentioning
confidence: 99%
“…Ready-to-eat food products, primarily fresh fruit and vegetables, usually dominate the available goods at these markets across the country [3][4][5][6]. With the growing number of farmers markets, consumers' demand for locally grown fresh fruit and vegetables has also increased [7]. This rise in fresh produce consumption may be attributed to an increased awareness about nutrition and enhancing healthy eating habits [8].…”
Section: Introductionmentioning
confidence: 99%
“…Efficient integration and application processes along with cover cropping in the long-term and sustainable use of animal manure can control pathogens [12], but there have been few studies investigating how cover crops influence the persistence of fecal bacteria in soil. Schutter et al [13] observed that season was the key determinant of microbial community structure, rather than winter or summer cover crop use; E. coli numbers declined as temperatures fell.…”
Section: Introductionmentioning
confidence: 99%